Hallmarks of Periodontitis - Benahmed, Asma Gasmi; Gasmi, Amin; Noor, Sadaf; Semenova, Yuliya; Emadali, Alireza; Dadar, Maryam; Shanaida, Yurii; Avdeev, Oleksandr; Bjørklund, Geir (Current Medicinal Chemistry, 2025)
Periodontitis is a complex polymicrobial disease of the oral cavity that affects tooth-supporting tissues. It is caused by multiple factors, such as pathogenic bacteria, genetic predisposition, and host immune response factors. The pathogenesis of periodontal disease involves the complex interrelations among bacterial toxins, several populations of cells, and host cell-secreted inflammatory mediators. Generally, periodontitis is characterized by the formation of intricate and varied biofilms of microbes on the tooth surface, commonly known as dental plaque. Activation of defense cells is characterized by releasing inflammatory mediators, such as proteases, acidic metabolites, cytokines, interleukins, and chemokines, which destroy tissue and ultimately cause bone resorption. The individual periodontal condition has a significant impact on systemic homeostasis, and its disruption can cause the development of some metabolic disorders. This review article summarizes the latest studies on the pathogenesis of periodontitis and describes the role of inflammatory mediators and genetic polymorphism in individuals, as well as relationships with some metabolic conditions. The information is collected from PubMed, Scopus, ScienceDirect, SpringerLink, and clinicaltrials.gov.
Keywords: inflammation